Penyuluhan Penanganan Cedera Olahraga Pada Pergelangan Kaki (Sprain Ankle) pada Komunitas Olahraga Sepakbola di MTS Bahrul Maghfiroh Malang - Aulia Nur Azizah; Nurul Aini Rahmawati; Lina Sriyatun (Rena Cipta Mandiri, 2024)
Introduction: An ankle sprain is an injury that occurs to the lateral complex ligaments due to overstretching in inversion and plantar flexion which occurs suddenly when the foot does not support perfectly on an uneven floor/ground surface. As a result of this injury several symptoms can occur such as pain, swelling and unstable ankle. Initial treatment uses RICE (rest, ice, compress, elevation), which aims to reduce pain and swelling as well as administering Teraband which aims to increase muscle strength and range of motion (ROM). Method : Providing counseling and application of exercise therapy carried out on October 23 2024 at 11.00 WIB at MTS Baghrul Magfiroh Jln.Joyo Agung No.2, Tlogomas, Kec.Lowokwaru, Malang City, East Java with 20 respondents. This activity uses posters, leaflets as health promotion media as well as filling out a questionnaire consisting of 4 questions with a value of 25 for each question. Results : There was a gain of 40% before being given an understanding and application of exercise therapy in the treatment of sports injuries to the ankle (ankle sprain). The results obtained were very significant in increasing understanding and handling of exercise therapy by 100% of the results given by respondents after providing counseling. Conclusion : There is an increase in understanding and application of exercise therapy in the initial treatment of sports injuries to the ankle (ankle sprain).